Pulse Width Modulation Control of Mecanum-Wheeled Mobile Robot With Random Noise - Ruijie Yin; Zhaojing Wu; Likang Feng (IEEE Access)
Pulse width modulation (PWM) control is investigated for the Mecanum-wheeled mobile robot (MWMR) driven by servo motors with random disturbance. As a preliminary, PWM strategy of random nonlinear systems is obtained by the aid of the functional analysis tool. A smooth voltage controller is presented by the backstepping technique for MWMR. Based on the boundedness of input voltage caused by direct-current motors, the optimal bounded controller is obtained by the quadratic programming method. Therefore, the optimal duty ratio is generated by the positive part and the negative part of the optimal control, the digital controller is synthesized in turns. Finally, a simulation example is given to demonstrate the efficiency of the proposed PWM scheme.